Optimisation for hot turning operations with multiple performance characteristics - Tosun, N; Ozler, L (Springer London Ltd, 2004)
This paper presents an investigation on the optimisation and the effect of cutting parameters on multiple performance characteristics (the tool life and the workpiece surface roughness) obtained by hot turning operations. A plan of experiments based on the Taguchi method was designed. M20 sintered carbide as tool and the high manganese steel as workpiece material were used in experiments. The workpiece material heated with liquid petroleum gas flame was machined under different settings of feed rate, depth of cut, cutting speed and workpiece temperature on a lathe. The results showed that cutting speed and feed rate were the dominant variables on multiple cutting performance characteristics. An optimum parameter combination was obtained by using statistical analysis.
Keywords: hot turning; tool life; surface roughness; Taguchi method; high manganese steel